Methodological Culture as One of the Necessary Conditions of Professional Skills of Future Teachers - Rasulova Mastura Saodat qizi (Genius Publishing Group, 2023)
This article talks about the fact that the formation of methodological culture in future teachers is one of the important conditions of their professional maturity, as well as the important components of methodological culture.
Keywords: Methodological culture; Intellectual sphere; Motivational sphere